The role of social support and spiritual wellbeing in predicting suicidal ideation among marginalized adolescents in Malaysia - Norhayati Ibrahim; Normah Che Din; Mahadir Ahmad; Noh Amit; Shazli Ezzat Ghazali; Suzaily Wahab; Nor Ba’yah Abdul Kadir; Fatimah Wati Halim; Mohd Radzi Tarmizi A. Halim (BMC Public Health, 2019)
Abstract Background The high number of adolescents and young adults harbouring suicidal ideation, as reported by the Ministry of Health Malaysia, is alarming. This cross-sectional study aims to examine the association between social support and spiritual wellbeing in predicting suicidal ideation among Malaysian adolescents. Methods A total of 176 adolescents in selected urban areas in the states of Wilayah Persekutuan and Selangor were selected. The Suicide Ideation Scale (SIS) was used to measure the level of severity or tendency of suicidal ideation. The Multidimensional Scale of Perceived Social Support (MSPSS) was used to measure the perceived social support received by the respondent while the Spiritual Wellbeing Scale (SWBS) was used to measure the religious wellbeing (RWB), the existential wellbeing (EWB) and the overall score of spiritual wellbeing (SWB). Results The study found that both RWB and EWB showed significant negative correlation with suicidal ideation. Similarly, support from family and friends also showed a negative correlation with suicidal ideation. Further analysis using multiple regressions showed that RWB and SWB, and family support predict suicidal ideation in adolescents. Conclusion Spiritual wellbeing in combination with family support plays a major role in predicting suicidal ideation. Therefore, intervention for encompassing spirituality and family support may contribute to a more positive outcome in suicidal adolescents.